2018
DOI: 10.14488/bjopm.2018.v15.n4.a5
|View full text |Cite
|
Sign up to set email alerts
|

ERP Implementation Project in a brewing manufacturer: the quality attribute as a performance differential

Abstract: This article aims to discuss the importance of the focus on quality attributes in an ERP system implementation project in a Brazilian brewing industry. The quality, as part of the "iron triangle" for conducting projects, can be monitored and associated with the project performance from the indicators associated to the quality attributes. The case study covered an Enterprise Resources Planning (ERP) system implementation on 6 business units of a brewing manufacturer distributed in different regions of Brazil, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…As mentioned in Literature Review, the integration between organizational functions impact the outcomes obtained (Nicoletti Junior et al, 2018;Reitsma and Hilletofth, 2018).Through the analyzed documentation and due to the specificity of certain risks, it was possible to identify that the risk activities have capillarity across all organizational functions (Oliva et al, 2019;Saeidi et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As mentioned in Literature Review, the integration between organizational functions impact the outcomes obtained (Nicoletti Junior et al, 2018;Reitsma and Hilletofth, 2018).Through the analyzed documentation and due to the specificity of certain risks, it was possible to identify that the risk activities have capillarity across all organizational functions (Oliva et al, 2019;Saeidi et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Risk management is not intended to eliminate an organization's business risks. Mitigating the impact of risks on the project performance presents a significant challenge for the stakeholders (Junior et al, 2018;Tan and Lee, 2022). It appears that risk management is an effective process for managers to make more assertive decisions for their companies, which is why companies adopt practices directly taken to their implementation (Meskovic and Zaimovic, 2021).…”
Section: Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Paid, Nicoletti Junior et al (2018) reviewed a study entitled ERP Implementation Project in a Beer Producer: Their Research was a Case Study in Brazil on Brewery Locations Including 6 Business Planning Systems Organizational resources (ERP) was the method of collecting information in their study through interview and questionnaire. They concluded that quality attribute is a differential function (Nicoletti Junior et al, 2018). Soares et al (2017) A study by title of the SERQUAL model by government higher education services found that tangibility was reported as the single most positive among the five proposed dimensions (Soares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%